Zn stable isotope fractionation during adsorption onto todorokite: A molecular perspective from X-ray absorption spectroscopy and density functional theory. (15th June 2022) - Wang, Zhao; Kwon, Kideok D.; Peacock, Caroline; Mo, Xinxin; Gou, Wenxian; Feng, Xionghan; Li, Wei
Abstract: Mineral-solution interface reactions control the mobility and fate of trace metals (e.g., Zn) and may drive their associated isotopic fractionation in the natural environment, but understanding the coupling between interfacial reactions and isotopic behavior requires a molecular-level understanding of these processes. In this study, we investigate Zn stable isotope fractionation during adsorption to todorokite as a function of reaction time, pH and Zn concentrations. We show that Zn stable isotope fractionation reaches equilibrium at ∼12 h reaction time at pH 6 and Zn concentrations of 0.05 mM. For Zn concentrations of 0.05 and 0.2 mM, Zn isotopic fractionation between adsorbed and aqueous Zn (Δ 66 Znadsorbed-aqueous ) is approximately −0.1 ± 0.04‰ at pH 3–5, and Δ 66 Znadsorbed-aqueous gradually increases from −0.1 ± 0.04‰ to 0.05 ± 0.05‰ at higher pH 6–8. Extended X-ray absorption fine structure (EXAFS) spectroscopy shows that Zn adsorbs to the todorokite surface as an outer-sphere octahedral complex with an average ZnO interatomic distance of 2.06 Å at pH 3. In contrast, Zn is predominantly present as a tetrahedral coordinated structure with a shorter average ZnO interatomic distance of ∼2.00–2.05 Å at pH 6 and 8, suggesting the presence of a mixture of octahedral outer-sphere and tetrahedral inner-sphere surface complexes. Density functional theory calculations suggest that outer-sphere surface complexes exist in the center of the structural tunnels of todorokite, yielding a theoretical Zn isotopic fractionation (Δ 66 Znadsorbed-aqueous ) of −0.2‰ to −0.3‰, whereas the tetrahedral inner-sphere surface complex results in a large Δ 66 Znadsorbed-aqueous of +0.5‰ to +0.8‰. Combined laboratory experiments and theoretical calculations demonstrate that different magnitudes of Zn isotopic fractionation are controlled by structural changes (e.g., coordination and bond distance) in the Zn surface complexes formed on todorokite relative to its aqueous form (i.e., aqua Zn(H2 O)6 2+ ). These results provide important new constraints for understanding Zn isotope signatures in natural Mn-rich sediments and lead to a more complete understanding of Zn isotopes in the ocean.